Profiling of Kidney Injury Biomarkers in Patients Receiving Cisplatin: Time‐dependent Changes in the Absence of Clinical Nephrotoxicity. Issue 4 (14th February 2017) - George, B; Wen, X; Mercke, N; Gomez, M; O'Bryant, C; Bowles, DW; Hu, Y; Hogan, SL; Joy, MS; Aleksunes, LM
Abstract : The success of cisplatin‐containing regimens to treat solid tumors is limited, in part, by nephrotoxicity. In rodents, several urinary proteins have emerged that are sensitive indicators of cisplatin‐induced kidney injury. We sought to characterize time‐dependent changes in the urinary concentrations of 12 proteins, including kidney injury molecule‐1 (KIM‐1), calbindin, beta 2‐microglobulin (β2M), and trefoil factor 3 (TFF3) after cisplatin therapy. Urine was collected at baseline, 3 days (range, 2–5 days), and 10 days (range, 9–11 days) from 57 patients with solid tumors receiving outpatient cisplatin therapy (≥25 mg/m 2 ). Serum creatinine was largely unchanged after cisplatin infusion. However, compared with baseline values, several novel biomarkers were significantly increased in the urine, including β2M, which was threefold higher by day 3 ( P < 0.0001). Urinary KIM‐1 and TFF3 were elevated twofold by day 10 ( P = 0.002 and P = 0.002, respectively), whereas calbindin levels were increased eightfold ( P < 0.0001). We report novel time‐dependent changes in the urinary excretion of noninvasive markers of subclinical kidney injury after cisplatin treatment.